2016
DOI: 10.4236/jss.2016.48012
|View full text |Cite
|
Sign up to set email alerts
|

Infertility in Sub-Saharan Africa: A Woman’s Issue for How Long? A Qualitative Review of Literature

Abstract: Infertility or childlessness is a major reproductive health issue for females as well as males respectively. Many couples suffer from infertility worldwide and in Sub-Saharan Africa, which has a cultural preference for high fertility; women shoulder the highest infertility consequences. The objective of this review was therefore to explore socially acceptable and culturally effective reproductive health strategies for the social management of infertility in sub-Sahara Africa. Different databases were searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 11 publications
1
31
0
2
Order By: Relevance
“…Failure of this often leads to unhappy married lives, divorces, and high levels of psychiatric morbidity [8]. Different studies have also shown that couples with infertility often face social stigmatization and are publically isolated [9]. Domestic violence and dissolution of marriage occur significantly more often among the infertile couples compared with couples in fecund relationships [8].…”
Section: Introductionmentioning
confidence: 99%
“…Failure of this often leads to unhappy married lives, divorces, and high levels of psychiatric morbidity [8]. Different studies have also shown that couples with infertility often face social stigmatization and are publically isolated [9]. Domestic violence and dissolution of marriage occur significantly more often among the infertile couples compared with couples in fecund relationships [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another reason couples may opt for traditional assistance is to avoid detection of a male factor and accompanying social blame [2, 28]. The fact that health-seekers often seek health care (conventional and traditional) concurrently and sequentially was earlier confirmed by others [2, 29, 30]. This study however showed that success was higher with those that received conventional hospital treatment than those receiving traditional treatment.…”
Section: Discussionmentioning
confidence: 83%
“…High cost of conventional therapy, cultural and religious beliefs, and societal pressure to conceive may influence a woman’s decision to seek traditional treatment [8]. Another reason couples may opt for traditional assistance is to avoid detection of a male factor and accompanying social blame [2, 28]. The fact that health-seekers often seek health care (conventional and traditional) concurrently and sequentially was earlier confirmed by others [2, 29, 30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infertility is socially constructed in many SSA cultures, that is, men and women are viewed and perceived to become parents and women are specially socialized to become mothers in society (Chimbatata & Malimba, 2016). This is an unambiguous contrast to other societies in the west and the affluent world where individuals or couples could choose not to have a child or just to have them by adoption.…”
Section: Infertility and Pcos: Interrelations Of Gender Roles And Sociocultural Expectationsmentioning
confidence: 99%